Answer:
Solution : Option A
Explanation:
What we want to do here is eliminate the parameter t. In order to do that, we can isolate t in our first equation x = t + 6 ----- ( 1 ) and then plug that value for t in the second equation y = 3t - 1. Our solution will be an equation that is not present with t.
( 1 ) x = t + 6, t = x - 6
( 2 ) y = 3( x - 6 ) - 1 ( Distribute the " 3 " in 3( x - 6 ) )
y = 3x - 18 - 1 ( Combine like terms )
y = 3x - 19
As you can see our result will be option a, y = 3x - 19.